MicroRNA-378 contributes to osteoarthritis by regulating chondrocyte autophagy and bone marrow mesenchymal stem cell chondrogenesis - Lu Feng; Zhengmeng Yang; Yucong Li; Qi Pan; Xiaoting Zhang; Xiaomin Wu; Jessica Hiu Tung Lo; Haixing Wang; Shanshan Bai; Xuan Lu; Ming Wang; Sien Lin; et al. (Elsevier, 2022)
Osteoarthritis (OA) is the most common joint disease; thus, understanding the pathological mechanisms of OA initiation and progression is critical for OA treatment. MicroRNAs (miRNAs) have been shown to be involved in the progression of osteoarthritis, one candidate is microRNA-378 (miR-378), which is highly expressed in the synovium of OA patients during late-stage disease, but its function and the underlying mechanisms of how it contributes to disease progression remain poorly understood. In this study, miR-378 transgenic (TG) mice were used to study the role of miR-378 in OA development. miR-378 TG mice developed spontaneous OA and also exaggerated surgery-induced disease progression. Upon in vitro OA induction, miR-378 expression was upregulated and correlated with elevated inflammation and chondrocyte hypertrophy. Chondrocytes isolated from articular cartilage from miR-378 TG mice showed impaired chondrogenic differentiation. The bone marrow mesenchymal stem cells (BMSCs) collected from miR-378 TG mice also showed repressed chondrogenesis compared with the control group. The autophagy-related protein Atg2a, as well as chondrogenesis regulator Sox6, were identified as downstream targets of miR-378. Ectopic expression of Atg2a and Sox6 rescued miR-378-repressed chondrocyte autophagy and BMSC chondrogenesis, respectively. Anti-miR-378 lentivirus intra-articular injection in an established OA mouse model was shown to ameliorate OA progression, promote articular regeneration, and repress hypertrophy. Atg2a and Sox6 were again confirmed to be the target of miR-378 in vivo. In conclusion, miR-378 amplified OA development via repressing chondrocyte autophagy and by inhibiting BMSCs chondrogenesis, thus indicating miR-378 may be a potential therapeutic target for OA treatments.